The Enhancement on Proton Conductivity of Stable Polyoxometalate‐Based Coordination Polymers by the Synergistic Effect of MultiProton Units. Issue 27 (31st May 2016) - Li, Jing; Cao, Xue‐Li; Wang, Yuan‐Yuan; Zhang, Shu‐Ran; Du, Dong‐Ying; Qin, Jun‐Sheng; Li, Shun‐Li; Su, Zhong‐Min; Lan, Ya‐Qian
Abstract: Two novel polyoxometalate (POM)‐based coordination polymers, namely, [Co(bpz)(Hbpz)][Co(SO4 )0.5 (H2 O)2 (bpz)]4 [PMo VI 8 Mo V 4 V IV 4 O42 ]⋅13 H2 O (NENU‐530 ) and [Ni2 (bpz)(Hbpz)3 (H2 O)2 ][PMo VI 8 Mo V 4 V IV 4 O44 ]⋅8 H2 O (NENU‐531 ) (H2 bpz=3, 3′, 5, 5′‐tetramethyl‐4, 4′‐bipyrazole), were isolated by hydrothermal methods, which represented 3D networks constructed by POM units, the protonated ligand and sulfate group. In contrast with most POM‐based coordination polymers, these two compounds exhibit exceptional excellent chemical and thermal stability. More importantly, NENU‐530 shows a high proton conductivity of 1.5×10 −3  S cm −1 at 75 °C and 98 % RH, which is one order of magnitude higher than that ofNENU‐531 . Furthermore, structural analysis and functional measurement successfully demonstrated that the introduction of sulfate group is favorable for proton conductivity. Herein, the syntheses, crystal structures, proton conductivity, and the relationship between structure and property are presented. Abstract : Taking charge : Two novel polyoxometalate (POM)‐based coordination polymers were isolated by hydrothermal reactions, which present 3D networks constructed by POMs, the protonated ligand and sulfate group.NENU‐530 shows a high proton conductivity of 1.5×10 −3  S cm −1 at 75 °C and 98 % relative humidity, which is one order of magnitude higher than that ofNENU‐531 .